Sovereign Suicide & Pathological Suicide [Suicidio Soberano y Suicidio Patológico] - Neira-Barrera, H (Universidad Nacional de Colombia, 2017)
In its definition of "suicide", the dictionary of the Spanish Royal Academy opts for a philosophical position that distances itself from some public health objectives and points of view, in order to emphasize the nature of suicide as an intimate act carried out by a subject capable of action. The boundaries of the concept are unclear: There is a continuum between suicide and death due to natural or accidental causes or reckless behavior. But suicide can only be the result of a sovereign act, and, therefore, someone who lacks will cannot be a suicide. This makes it possible to discuss the proposals of B. Spinoza and I. Kant, as well as some of the public health approaches that disregard the sovereign nature of suicide.